FAKTOR PENDORONG ALIH FUNGSI LAHAN KAKAO MENJADI KELAPA SAWIT DI DESA LEMBAH SUBUR KECAMATAN DANGIA KABUPATEN KOLAKA TIMUR - Kukuh Prio Pinandito; Ima Astuty Wunawarsih; Putu Arimbawa; Darsilan Dima (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The conversion of agricultural land is one of the phenomena that occurs quite often at present in the use of land. This is in accordance with economic principles, namely that activities that are considered unproductive and unprofitable are always quickly replaced by other activities that are more productive and profitable. This research aims to determine the driving factors and typology of the conversion of cocoa plantations into palm oil plantations in the Subur Valley Village. Purposive determination of research location. The population in this research is cocoa farmers who convert agricultural land into palm oil plantations in the village of iSur Valley, totaling 27 people using census techniques. The data analysis used is Multiple Logistic Regression, and Descriptive Analysis. The results of the research show that economic factors and social factors have an influence on the farmer's decision to transfer the agricultural function of Cocoa to Palm Oil. Meanwhile, technical factors do not influence the farmer's decision to transfer the agricultural function of Cocoa to Palm Oil. The typology of land use conversion from cocoa to palm oil palm plantations in Lembah Subur Village is divided into three types, namely Gradual land use change with a Sporadic pattern, Systematic land use change over an Enclave pattern, and a combination of Gradual land use using a Sporadic pattern and Systematic land use using an Enclave pattern.